Performance of the new biological small‐ and wide‐angle X‐ray scattering beamline 13A at the Taiwan Photon Source. Issue 2 (18th March 2022) - Shih, O.; Liao, K.-F.; Yeh, Y.-Q.; Su, C.-J.; Wang, C.-A.; Chang, J.-W.; Wu, W.-R.; Liang, C.-C.; Lin, C.-Y.; Lee, T.-H.; Chang, C.-H.; Chiang, L.-C.; et al.
Abstract : A new endstation for biological small‐ and wide‐angle X‐ray scattering is detailed, which provides development opportunities for studying correlated local and global structures of biomolecules in solution. Abstract : Recent developments in the instrumentation and data analysis of synchrotron small‐angle X‐ray scattering (SAXS) on biomolecules in solution have made biological SAXS (BioSAXS) a mature and popular tool in structural biology. This article reports on an advanced endstation developed at beamline 13A of the 3.0 GeV Taiwan Photon Source for biological small‐ and wide‐angle X‐ray scattering (SAXS–WAXS or SWAXS). The endstation features an in‐vacuum SWAXS detection system comprising two mobile area detectors (Eiger X 9M/1M) and an online size‐exclusion chromatography system incorporating several optical probes including a UV–Vis absorption spectrometer and refractometer. The instrumentation and automation allow simultaneous SAXS–WAXS data collection and data reduction for high‐throughput biomolecular conformation and composition determinations. The performance of the endstation is illustrated with the SWAXS data collected for several model proteins in solution, covering a scattering vector magnitude q across three orders of magnitude. The crystal‐model fittings to the data in the q range ∼0.005–2.0 Å −1 indicate high similarity of the solution structures of the proteins to their crystalline forms, except for some subtle hydration‐dependent local details. These results open up new horizons of SWAXS in studying correlated local and global structures of biomolecules in solution.